An investigation of temporal change in lithic technology at Grassridge Rockshelter, Eastern Cape South Africa - Mdludlu, Ayanda (Department of Archaeology, 2023)
This thesis discusses the lithic technological change in Grassridge Rockshelter, a multi-component site located in the interior region of the Eastern Cape of South Africa that presents a rich high-resolution stratigraphy that interchanges with periods of hiatuses between the Late Pleistocene (LP) dated to about ~43ka, Terminal Pleistocene (TP) dated to ~13ka and Mid-Holocene (MH) occupations dated to ~7ka. The similarities and differences between the LP and TP as well as the TP and MH lithic assemblages are analysed to better understand the behaviours of toolmakers. The analyses use raw material type choices and numerous lithic tool typologies as proxies to track lithic variability. Also considered in this study are tool traits that include platform treatment, external platform angle, platform thickness, early/late debitage exploitation, length over width ratio, profile, and width over thickness ratio. The frequencies of each tool trait are arranged into Tostevin's (2012) methodology system of knapping behaviours to consider various explanations – environmental, economic, and sociocultural- for these variations.